Hypoxia increases the metastatic ability of breast cancer cells via upregulation of CXCR4 - Redmond H Paul; Cronin Patricia A; Wang Jiang H (BMC Cancer, 2010)
Abstract Background Chemokine SDF1α and its unique receptor CXCR4 have been implicated in organ-specific metastases of many cancers including breast cancer. Hypoxia is a common feature of solid tumors and is associated with their malignant phenotype. We hypothesized that hypoxia would upregulate CXCR4 expression and lead to increased chemotactic responsiveness to its specific ligand SDF1α. Methods Three breast cancer cell lines MDA-MB-231, MCF7 and 4T1 were subjected to 48 hrs of hypoxia or normoxia. Cell surface receptor expression was evaluated using flow cytometry. An extracellular matrix invasion assay and microporous migration assay was used to assess chemotactic response and metastatic ability. Results CXCR4 surface expression was significantly increased in the two human breast cancer cell lines, MDA-MB-231 and MCF7, following exposure to hypoxia. This upregulation of CXCR4 cell surface expression corresponded to a significant increase in migration and invasion in response to SDF1-α in vitro. The increase in metastatic potential of both the normoxic and the hypoxic treated breast cancer cell lines was attenuated by neutralization of CXCR4 with a CXCR4 neutralizing mAb, MAB172 or a CXCR4 antagonist, AMD3100, showing the relationship between CXCR4 overexpression and increased chemotactic responsiveness. Conclusions CXCR4 expression can be modulated by the tissue microenvironment such as hypoxia. Upregulation of CXCR4 is associated with increased migratory and invasive potential and this effect can be abrogated by CXCR4 inhibition. Chemokine receptor CXCR4 is a potential therapeutic target in the adjuvant treatment of breast cancer.